GENDER AWARENESS DALAM KELUARGA MUSLIM - Mustabsyirah M. Husein (Pusat Studi Wanita UIN Ar-Raniry, 2017)
Gender equality and equity is not a strange matter anymore in talks. Islam has well introduced equal opportunity concept between men and women. Therefore, to understand it is a must. A good perception of the Islamic perspective of gender in Muslim family will results empowerment toward men, women, and couple, and create a good relationship among each other in a family. This activity necessitates balances between husband and wife both in efforts and results. Growth and development of the good relationship in a family are one of the outcomes of motivation and norms application given based on equality that whoever, men and women as godly human beings, do good things will get the same and not be mistreated.